"I intend to have this book retranslated": Translation in Joseph Goebbels's diaries. Issue 1 (2nd January 2020) - Van linthout, Ine
ABSTRACT: Joseph Goebbels, Propaganda Minister in the Third Reich, kept a diary during the twelve years of Nazi dictatorship. In spite of the pitfalls associated with diaries as a historical source, Goebbels's entries on translated literature prove meaningful for the history of translation during the Nazi regime. The entries shed light on Goebbels's reading of translated literature and the different functions he attributes to it. They reveal a significant politicisation in his thinking about translation, improve our understanding of his agency in translation matters and provide insights into the motivations that inform the Propaganda Minister's decision-making around translated texts. By investigating this historical source which has not been considered from the point of translation so far, the present article aims to contribute a fresh perspective on the workings of translation policy in Nazi Germany.